Air velocity and exposure time to ventilation affect body surface and rectal temperature of broiler chickens - Furlan, R. L.; Macari, M.; Secato, E. R.; Guerreiro, J. R.; Malheiros, E. B. (Elsevier, 2000)
Increasing air movement over poultry by using fans (ventilation) has become an accepted means of reducing environmental heat stress over the last several years. The purpose of this study was to evaluate the effect of air velocity and exposure time to ventilation on body surface and rectal temperature of broiler chickens. Male broiler chickens ages 36-42 days were placed in individual wire cages and exosed to five different air velocities (5.7, 4.2, 3.1, 2.4, or 1.8 m/sec). Throughout the experimental head, back, leg, and rectal temperatures were monitored every 10 min during a 30-min period for each air velocity. The data showed that exposure time to the wind affected (P<.05) leg and body temperature, with a rapid reduction being observed during the first 10 min. There was a reduction in leg temperature with air velocity of 2 m/sec; however, air velocity lower than 4.5 m/sec was not effective in decreasing head and back temperature. The results suggest that air velocity of 2 m/sec, in air temperature of 29°C, improves heat loss in the birds. The data also indicate that exposure time to ventilation seems to be a critical point in the maintenance of bird thermal homeostasis.
Keywords: Air velocity; Body temperature; Broiler chicken; Heat stress; Surface temperature